Sagehood and Supererogation in the Analects. Issue 2 (June 2013) - Connolly, Timothy
Abstract The Confucian ethical tradition emphasizes unceasing progress toward the goal of sagehood, and so it is generally opposed to the idea of supererogation, as this implies that we may be satisfied with attaining some sub‐sagely level of morality. The one possible exception to this anti‐supererogationist stance, however, turns out to be Confucius himself, who in the Analects appears to downplay sagehood and instead focus on the goal of junzi. Yet given that Confucius stresses ceaseless cultivation as much as anyone else in the tradition, this leaves us with a puzzle about the sage's status in the Analects. Is sagehood supererogatory?